2018
DOI: 10.3389/fphys.2018.01019
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of Sister Chromatids Separation Promotes Progression of Hepatocellular Carcinoma According to Analysis of Gene Expression Profiling

Abstract: Despite studying the various molecular mechanisms of hepatocellular carcinoma (HCC), effective drugs and biomarkers in HCC therapy are still scarce. The present study was designed to investigate dysregulated pathways, novel biomarkers and therapeutic targets for HCC. The gene expression dataset of GSE14520, which included 362 tumor and their paired non-tumor tissues of HCC, was extracted for processing by the Robust multi-array average (RMA) algorithm in the R environment. SAM methods were leveraged to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 77 publications
2
10
0
Order By: Relevance
“…Among them, 386 genes were upregulated and 271 genes were downregulated. The results of GO and KEGG analyses revealed that biological processes and pathways were enriched in cell cycle-associated processes, which is congruent to the results obtained in previous studies (9,43). The present study also demonstrated that the oxidation-reduction process was the most significant in HCC.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Among them, 386 genes were upregulated and 271 genes were downregulated. The results of GO and KEGG analyses revealed that biological processes and pathways were enriched in cell cycle-associated processes, which is congruent to the results obtained in previous studies (9,43). The present study also demonstrated that the oxidation-reduction process was the most significant in HCC.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present study demonstrated that CCNB2, CDC20, MAD2L1, MCM2, CENPF and BUB1B were important to HCC and may directly or indirectly regulate its progression. These results were partially congruent with a previous study, which indicated that CENPF and BUB1B were good predictors of HCC therapy (9). In addition, CCNB2 is key protein of the cyclin family and regulates the progression of the G2/M transition during the cell cycle (46).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For the second chemoradiotherapy of recurrent and metastatic esophageal cancer, the potential efficacy of taxanes is reduced, due to the detection of BUB1B (13). As an important molecule in the formation of mitotic spindles, the application value of BUB1B as a drug target or biomarker in the diagnosis and treatment of hepatocellular carcinoma and primitive neuroectodermal tumors is constantly being explored (14,15). Clinically, Figure 7 RNA transport pathway (the chart is from the KEGG database, gene symbolized by ★ and correlation P values can be found in Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Low expression of BUB1B is associated with the poor survival of patients with colon adenocarcinomas and lung cancer, however overexpression of BUB1B contributes to the progression and recurrence of gastric cancer and bladder cancer (35). However, several studies showed that the overexpression of BUB1B is associated with worse prognosis in patients with HCC (36,37).…”
Section: Discussionmentioning
confidence: 99%